PROTOTYPE OF IRRIGATION SLUICE GATE DISTRIBUTION USING ARDUINO-BASED TINY RTC MODULE - Rohman, Efi; Swastika, Rulin; Suawrdi, Suawrdi; Akbar, Sahrul (Institut Bakti Nusantara, 2023)
Technological advances in the era of globalization have been increasing rapidly, especially in agriculture. Currently, many robotics companies around the world are competing to create sophisticated equipment in an effort to increase agricultural productivity. Irrigation is an important part of agriculture. With the irrigation channels, it makes it easier for farmers to water crops. To distribute water fairly and evenly, this requires primary irrigation channels that are continuous. Also, in order to align cropping patterns, an irrigation sluice gate is needed in the primary canal that can be opened and closed automatically according to a predetermined schedule. The purpose of this research is to produce a tool in the form of a prototype for water distribution and automatic opening and closing of irrigation doors using the Arduino-based Tiny RTC module. The method used in this study is a method of drawing using flowcharts and making programs using the Arduino IDE. The results of this study are a prototype of water distribution and automatic opening and closing of irrigation doors using the Arduino-based Tiny RTC module.